Dearomatization of aryl sulfoxides: a switch between mono- and dual-difluoroalkylation. Issue 11 (27th February 2020) - Huang, Xin; Zhang, Yage; Liang, Weijian; Zhang, Qifeng; Zhan, Yaling; Kong, Lichun; Peng, Bo
Abstract : Herein we describe the dearomatization of aryl sulfoxides with difluoroenol silyl ether (DFESE) using a rearrangement/addition protocol. Abstract : Herein we describe the dearomatization of aryl sulfoxides with difluoroenol silyl ether (DFESE) using a rearrangement/addition protocol. The selection of the sulfoxide activator determines whether one or two difluoroalkyl groups are incorporated into dearomatized products. Using TFAA can deliberately halt the reaction at the mono-difluoroalkylated dearomatized intermediate formed via a [3, 3]-rearrangement, which can be further trapped by external nucleophiles to give mono-difluoroalkylated alicycles. In contrast, switching to Tf2 O enhances the electrophilicity of dearomatized intermediates, thus allowing for the adoption of a second DFESE to produce dual-difluoroalkylated alicycles.